2014
DOI: 10.1515/mammalia-2013-0139
|View full text |Cite
|
Sign up to set email alerts
|

Does livestock influence the diet of Iberian ibex Capra pyrenaica in the Peneda-Gerês National Park (Portugal)?

Abstract: Abstract:We carried out a pilot study about the influence of the domestic goat Capra hircus on the feeding ecology of the Iberian ibex Capra pyrenaica in the Peneda-Gerês National Park (PGNP, Portugal). We mapped the grazing areas of domestic goat flocks and determined their stocking rates in two mountains of PGNP, Gerês and Amarela, and we investigated the diets of both ungulates using fecal microhistology in an area where they partially overlapped during spring and summer. Diet composition, ligneous diversit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Some parishes with low GLDI may supply grass (or grazing land) to farm holdings in other parishes with more cattle. Although cattle are decreasing in the PGNP, some species such as horses and cows graze in a free-ranging regime throughout the year, with possible conflicts (competition for resources) with wildlife, namely the wild goat, as reported by Moço et al [48]. The major implication of the decrease in reared animals is the likely decrease in food supply in a region that holds potential (grasslands, local breeds) for growing cattle in a traditional and sustainable way.…”
Section: Reared Animalsmentioning
confidence: 93%
“…Some parishes with low GLDI may supply grass (or grazing land) to farm holdings in other parishes with more cattle. Although cattle are decreasing in the PGNP, some species such as horses and cows graze in a free-ranging regime throughout the year, with possible conflicts (competition for resources) with wildlife, namely the wild goat, as reported by Moço et al [48]. The major implication of the decrease in reared animals is the likely decrease in food supply in a region that holds potential (grasslands, local breeds) for growing cattle in a traditional and sustainable way.…”
Section: Reared Animalsmentioning
confidence: 93%
“…The morphological characteristic of the samples does not always allow for correct species assessment (Monterroso et al, 2019). In this study, one of the samples fieldassigned to Iberian ibex was also shown to contain fecal DNA of domestic goats, highlighting the strong sympatry of these species in the Gerês east nuclei (Moço et al, 2014). Molecular host species identification thus prevented the inclusion of one mixed-species sample that could otherwise compromise the results.…”
Section: Discussionmentioning
confidence: 79%
“…The Gerês‐Xurés Transboundary Biosphere Reserve (GXTBR, 41°43′49.22″N 8°9′42.05″W, max elevation: 1546 m) currently holds the single population of Iberian ibex in Portugal, estimated in 2011–2012 at 576 individuals (CI 95 356–930) in four geographical nuclei: Gerês east, Gerês west, Serra Amarela, and Castro Laboreiro (Fonseca et al, 2017 ; Moço et al, 2006 ). Among the threats to the conservation of this population is cohabitation with livestock, mediated by competition and pathogen transmission (Acevedo et al, 2007 ; Fonseca et al, 2017 ; Moço et al, 2014 ; Walker & Morgan, 2014 ). The Iberian ibex population at GXTBR lives in sympatry with a large population of extensively managed domestic goats, Capra hircus (>16,000 in 2019–INE, 2022 ), many under organic production systems (Gandra et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, interest in this subspecies has surged enough to motivate researchers to a controversial cloning attempt (Folch et al 2009;Kupferschmidt 2014). Initiatives to re-establish populations of the Iberian ibex have been taken across the Iberian Peninsula, where a population of the subspecies C. p. victoriae now occurs in the former range of C. p. lusitanica (Moço et al 2006(Moço et al , 2015. Plans to relocate C. p. victoriae also into the historical range of C. p. pyrenaica (Crampe 1991) have been enacted by releasing and monitoring of animals since 2014 onwards (Crampe et al 2015).…”
Section: Introductionmentioning
confidence: 99%